NKD1 marks intestinal and liver tumors linked to aberrant Wnt signaling - Stancikova, Jitka; Krausova, Michaela; Kolar, Michal; Fafilek, Bohumil; Svec, Jiri; Sedlacek, Radislav; Neroldova, Magdalena; Dobes, Jan; Horazna, Monika; Janeckova, Lucie; Vojtechova, Martina; Oliverius, Martin; et al. (Cellular signalling, 2015)
The activity of the Wnt pathway undergoes complex regulation to ensure proper functioning of this principal signaling mechanism during development of adult tissues. The regulation may occur at several levels and includes both positive and negative feedback loops. In the present study we employed one of such negative feedback regulators, naked cuticle homolog 1 (Nkd1), to follow the Wnt pathway activity in the intestine and liver and in neoplasia originated in these organs. Using lineage tracing in transgenic mice we localized Nkd1 mRNA to the bottom parts of the small intestinal crypts and hepatocytes surrounding the central vein of the hepatic lobule. Furthermore, in two mouse models of intestinal tumorigenesis, Nkd1 expression levels were elevated in tumors when compared to healthy tissue. We utilized a collection of human intestinal polyps and carcinomas to confirm that NKD1 represents a robust marker of neoplastic growth. In addition, expression analysis of NKD1 in liver cancer showed that high expression levels of the gene distinguish a subclass of hepatocellular carcinomas related to aberrant Wnt signaling. Finally, our results were confirmed by bioinformatic analysis of large publicly available datasets that included gene expression profiling and high-throughput sequencing data of human colon and liver cancer specimens.
Keywords: hepatocyty; Adaptor Proteins, Signal Transducing; RNA, Messenger; kolorektální nádory; mutace; NKD1; Wnt signaling; Transcription, Genetic; beta Catenin; signální transdukce; Intestine; Carcinoma, Hepatocellular; Adenomatous Polyposis Coli Protein; proteiny Wnt; Hepatocellular carcinoma; Signal Transduction; Wnt Proteins; Hepatocytes; genetická transkripce; Carrier Proteins; Colorectal cancer; Animals; lidé; myši transgenní; nádory jater; Humans; zvířata; střevní nádory; Calcium-Binding Proteins; Intestinal Neoplasms; adaptorové proteiny signální transdukční; hepatocelulární karcinom; myši; Mice, Transgenic; proteiny vázající vápník; Colorectal Neoplasms; protein familiární adenomatózní polypózy; Mutation; Liver; Liver Neoplasms; Mice; messenger RNA; transportní proteiny; beta-katenin